CSS Mastery Advanced Web Standards Solutions - Budd, Andy; Collison, Simon; Moll, Cameron (Friends of Ed [Imprint] New York : Apress L. P., 2006)
Annotation This book is your indispensable guide to cutting-edge CSS development—all you need to work your way up to CSS professional.While CSS is a relatively simple technology to learn, it is a difficult one to master. When you first start developing sites using CSS, you will come across all kinds of infuriating browser bugs and inconsistencies. It sometimes feels like there are a million and one different techniques to master, spread across a bewildering array of websites. The range of possibilities seems endless and makes for a steep and daunting learning curve.By bringing all of the latest tips, tricks, and techniques together in one handy reference, this book demystifies the secrets of CSS and makes the journey to CSS mastery as simple and painless as possible. While most books concentrate on basic skills, this one is different, assuming that you already know the basics and why you should be using CSS in your work, and concentrating mainly on advanced techniques.It begins with a brief recap of CSS fundamentals such as the importance of meaningful markup, how to structure and maintain your code, and how the CSS layout model really works.With the basics out of the way, each subsequent chapter details a particular aspect of CSS-based design. Through a series of easy-to-follow tutorials, you will learn practical CSS techniques you can immediately start using in your daily work. Browser inconsistencies are the thorn in most CSS developers' sides, so we have dedicated two whole chapters to CSS hacks, filters, and bug fixing, as well as looking at image replacement; professional link, form, and list styling; pure CSS layouts; and much more.All of these techniques are then put into practice in two beautifully designed case studies, written by two of the world's best CSS designers,Simon CollisonandCameron Moll.
Trade